Reconceptualizing Spiritual Authority: A Dialogical and Epistemic Approach to Theological Anthropology and Formation in the Age of Generation Z - Vinus Zai; Dwi Lestari Ningsih (Jurnal Theologia, 2026)
This article examines spiritual authority in theological higher education as a multidimensional construct shaping the ethical and character formation of Generation Z students in Indonesia. The unit of analysis focuses on the conceptual relationship between spiritual authority, epistemic authority, and character formation within contemporary theological learning environments. The study aims to reconceptualize spiritual authority beyond hierarchical domination into a dialogical, epistemic, and formative framework responsive to digital-era learners. Employing a qualitative conceptual approach based on critical literature analysis, the article integrates theological reflection, Michael Polanyi’s epistemology of personal knowledge, and socio-cultural insights from Indonesian intellectual discourse. The study finds that traditional models of authority as unilateral knowledge transmission are increasingly ineffective among Generation Z, who engage knowledge through decentralized and interactive platforms. As a result, spiritual authority must be reframed as epistemic guidance, where lecturers function as “wisdom curators” who facilitate discernment, integrate knowledge, and cultivate responsible freedom within a community of inquiry. This reconceptualization constitutes the article’s primary novelty, offering a dialogical model of authority that is both theologically grounded and pedagogically adaptive. The article contributes to the discourse on theological education by proposing a framework in which spiritual authority operates as formative stewardship, enabling the development of altruism, resilience, and vocational integrity in contemporary students.